2018
DOI: 10.1002/chem.201805006
|View full text |Cite
|
Sign up to set email alerts
|

Versatility in the Brook Rearrangement for the Selective Ring‐Opening of Three‐Membered Rings

Abstract: From a single α‐silylated carbinol intermediate, easily accessible by carbometallation of cyclopropenes, various scaffolds featuring a quaternary carbon stereocenter could be obtained selectively. The selectivity towards these different products was achieved by either changing the experimental conditions or the nature of the organometallic species involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 83 publications
0
12
1
Order By: Relevance
“…We have identified a new rearrangement of vinylcyclopropane into skipped dienes with a stereogenic centre at the central position. Conversely to previously reported rearrangements, this rearrangement was found to be very selective and proceed at room temperature (15 min, r.t., TiCl 4 catalysis). Based on deuteration experiments we proposed a mechanism for this transformation which involves a regioselective ring‐opening of the cyclopropane followed by a 1,2‐migration of an aryl group.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…We have identified a new rearrangement of vinylcyclopropane into skipped dienes with a stereogenic centre at the central position. Conversely to previously reported rearrangements, this rearrangement was found to be very selective and proceed at room temperature (15 min, r.t., TiCl 4 catalysis). Based on deuteration experiments we proposed a mechanism for this transformation which involves a regioselective ring‐opening of the cyclopropane followed by a 1,2‐migration of an aryl group.…”
Section: Resultscontrasting
confidence: 86%
“…This latter, unlike 3 , was found to be unreactive upon MgI 2 catalysis. We now have attempted other reaction conditions to rearrange 5aa and, interestingly, found that it leads quantitatively to skipped diene 6aa in the presence of TiCl 4 or FeCl 3 …”
Section: Introductionmentioning
confidence: 99%
“…However, when the same intermediates 39 were added to a magnesiate reagent, Bu 3 MgLi, the intermediate ate complexes underwent the Brook rearrangement followed by ring fragmentation. This sequence provides silyl enol ethers 41 in good yields as single geometrical Z isomers, as illustrated in Scheme , path b . Even more fascinating is the observation that the same intermediates 39 treated with a dialkylmagnesium species Bu 2 Mg, provide now skipped dienes possessing the quaternary stereocenter were formed (Scheme , path c) …”
Section: Metal-mediated Ring Cleavagementioning
confidence: 99%
“…This sequence provides silyl enol ethers 41 in good yields as single geometrical Z isomers, as illustrated in Scheme , path b . Even more fascinating is the observation that the same intermediates 39 treated with a dialkylmagnesium species Bu 2 Mg, provide now skipped dienes possessing the quaternary stereocenter were formed (Scheme , path c) …”
Section: Metal-mediated Ring Cleavagementioning
confidence: 99%
“…The last piece of work at the moment described the synthesis of γ,δ-unsaturated ketones 276 decorated with a quaternary carbon at β-position (Scheme 40C). 193 Once α-silylcarbinolate intermediates were generated from cyclopropenes 275, treatment with two equivalents of n-BuLi, subsequent increase of the temperature and final hydrolysis afforded ketones 276 in moderate overall yields. Again, transfer of chirality was viable as illustrated with the preparation of 276d from the enantioenriched cyclopropene.…”
Section: Metalation Reactions Of Cyclopropenes Involving C−c Bond Cle...mentioning
confidence: 99%